Recognizing Acupuncture Therapist and Services - Wijanto, Chrise; Tamtomo, Didik; Joebagyo, Hermanu (Journal of Health Policy and Management, 2019)
Background: Acupuncture services in Indonesia keep developing. Law No. 36 of 2014 concerning health personnel has confirmed the status of acupuncture in Indonesia. The regulation includes acupuncture health personnel in the physical therapy group not as traditional ones. However, there are still scientific publications in 2018 which state that acupuncture services are traditional health services. This study aimed to describe the services of acupuncture and acupuncture health personnel.Subjects and Method: This was a qualitative descriptive one. It was conducted in Surakarta City in November 2018-January 2019. It employed a purposive sampling technique to determine informants. The informants in this study consisted of 5 informants, namely 1 executive board of the Indonesian therapist acupuncture association (HAKTI) center, 1 Central Java HAKTI administrator, 1 Surakarta Ministry of Health Polytechnic lecturer at the Acupuncture Department, and 2 therapists and acupuncture service providers. The data collection in this study was done using the technique of in-depth interviews, observation, and document analysis. The data analysis was conducted using the method of Miles and Huberman.Results: Acupuncture service is an effort to restore non-pharmacological health using therapy or needle stabbing to help smooth the flow of energy and blood so that the body can be healthier by acupuncturists with a minimum of three diploma education. Minister of Health Regulation No. 34 of 2018 is a special regulation on licensing and the practice of therapist acupuncturists. The purpose of this regulation is to provide a legal protection for health care personnel who are acupuncturists who are about to practice, both practice independently and join health care facilities. This regulation is appropriate because it writes health centers as one of the acupuncture services. receiving acupuncture services, until now the acupuncture service has no definite provisions regarding service fees.Conclusion: Acupuncture service is health recovery efforts using needle puncture techniques. Acupuncture therapists are acupuncturists in the physical ignition group.Keywords: acupuncture therapist, acupuncture serviceCorrespondence: Chrise Wijanto. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: chrisewijanto@yahoo.com. Mobile: +6285725873639.Journal of Health Policy and Management (2019), 4(2): 128-138https://doi.org/10.26911/thejhpm.2019.04.02.08